Adaptasi Siswa dalam Pembelajaran Daring di Era 4.0 Pada Masa Pandemi Covid-19 - Siti Sultonah; Septi Kuntari (Teacher Training and Education Faculty, of Widya Gama Mahakam Samarinda University, 2021)
The research was conducted to explain how the impacts of the existence of Covid-19, especially in the education sector, describe the problems and obstacles experienced by students during online learning, assess the adaptation of students in taking online learning and the implications of the industrial revolution 4.0 on the use of digital technology as an alternative solution. In learning during the Covid-19 pandemic, the research method used was qualitative where the sample in this study were high school students in the Sobang sub-district. Data collection was carried out by compiling various sources in the form of mass media, observation and supported by interview result. Processed and analyzed then presented in the form of narrative sentences. The results of this study indicate that the impact of the Covid-19 pandemic has caused rapid social change in education which requires students to adapt to the learning process an online. The students adaptations include learning and understanding what is meant by independent online learning by relying on Youtube and Google. And the result are now students are starting to become proficient in using technology and various online media to support learning thanks to the adaptations made. Because the implementation of online learning encourages students to strive to improve their competence in terms of mastery of technology in the digital era 4.0 to support learning during a pandemic.